2009
DOI: 10.1097/naq.0b013e3181b9dcf8
|View full text |Cite
|
Sign up to set email alerts
|

Creating a Culture of Innovation in Nursing Education Through Shared Vision, Leadership, Interdisciplinary Partnerships, and Positive Deviance

Abstract: Although innovation is typically viewed by healthcare and academic institutions, business leaders, entrepreneurs, and private corporations as necessary for continuous improvement, high-quality care, and scientific advancement, barriers in creating and sustaining innovative academic environments abound and require effective leadership to overcome them. Therefore, the purpose of this article is to describe the major barriers and facilitators to innovation in colleges of nursing and healthcare professions along w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 3 publications
0
20
0
Order By: Relevance
“…An excellent example would be the development of a model of inter-professional education that could enhance care through better collaboration across health disciplines in health care settings. [30][31][32][33][34] …”
Section: Discussionmentioning
confidence: 99%
“…An excellent example would be the development of a model of inter-professional education that could enhance care through better collaboration across health disciplines in health care settings. [30][31][32][33][34] …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Adams et al, (2006) Beheshtifar and Shariatifar (2013) and Zheng et al (2010) reported significant relationship between organizational structure, culture and innovation. Further, Apekey et al, (2011), Melnyk and Davidson (2009) and Tahseen (2013) found that organizational culture and leadership promote innovation. Rainey (2006) and Muller et al (2005) also found significant relationship between organizational strategy, leadership and innovation.…”
Section: Entrepreneurial Architecture (Ea)mentioning
confidence: 99%
“…Mutually beneficial academic-clinical partnerships are both an indicator and a driver of innovation; “the solving of real-world complex healthcare problems is sparked and enhanced through interdisciplinary partnerships” (Melnyk & Davidson, 2009). Healthy partnerships can benefit students and their university or college, as well as help health care institutions earn special notation from their Magnet® reviewers (Moscato, Miller, Logsdon, Weinberg, & Chorpenning, 2007) and increase staff satisfaction.…”
Section: The Clinical Nurse Fellowshipmentioning
confidence: 99%